The Role of Parents in Socialization of Children and Adolescents in the Juvenile Home (Journal of Universal Excellence, 2026)
Research question: What is the importance of education and socialization of adolescents and children and parental roles in Maribor juvenile centre during their living there?Purpose: We want to establish whether it is necessary to consider the difference between education and socialization when working with adolescents and children.Methods: The research was carried out at the Maribor juvenile centre where 82 children and adolescents resided at the time of the quantitative survey, and 70 of them answered the questionnaire.Results: Children and adolescent consider cooperation with parents the least important. Among other things, we analysed indicators such as: educator's professionalism, interpersonal relationships, internal working conditions, and values in relation to work with children and adolescents. We were interested in the importance of parents in education and socialization of children in Maribor juvenile centre.Organization: The study identified the role of parents of children with emotional deficits in institutional care in the education and socialization of children.Society: The contribution is important from the perspective of the lives of children and adolescents in Maribor juvenile centre and the coexistence of children and adolescents and their parents, as well as the educators employed by the institution.Originality: This is the first such comprehensive study conducted among children and adolescents with emotional deficits.Research limitations/further research: A limitation of the research is that children and adolescents, and partly educators, were included. In further research, it will be necessary to involve more parents who are an important actor in education and work with their children in the institution.
Keywords: children; adolescents; parents; education; socialization; home